First-principles prediction of Tl/SiC for valleytronics. Issue 39 (3rd October 2017) - Xu, Zhen; Zhang, Qingyun; Shen, Qian; Cheng, Yingchun; Schwingenschlögl, Udo; Huang, Wei
Abstract : We demonstrate by first-principles calculations that monolayer Tl can be grown on SiC. Our study shows that the Tl/SiC system is promising for valleytronic applications. Abstract : Recently, monolayer Tl on a Si or Ge substrate has been proposed for potential valleytronic systems. However, the band gaps of these systems are less than 0.1 eV, which is too small to be applied because an electric field or magnetic doping will reduce the band gaps further for the systems to become metallic. Here, we investigate SiC as an alternative substrate. By first-principles calculations we demonstrate that monolayer Tl can be grown on SiC. There are two valleys around the K / K ′ points and the Berry curvature shows that the two valleys are inequivalent, indicating valley pseudospin. Moreover, due to the larger band gap of SiC (3.3 eV), the band gap of the Tl/SiC system is 0.6 eV, which is large enough for valley manipulation. Furthermore, we demonstrate that Cr doping can achieve valley polarization. Our study shows that the Tl/SiC system is promising for valleytronic applications.